Patient and professional perceptions of metabolic syndrome and its management: a qualitative study in the United Arab Emirates - Alozaibi, Naseeba (2011)
Metabolic syndrome (MetS) is defined as the clustering of medical conditions (that is impaired fasting glucose (IFG) or type 2 diabetes mellitus (T2DM), hypertension (HTN), obesity and dyslipidaemia) that increase an individual's risk of developing diabetes or cardiovascular diseases (CVD). In the United Arab Emirates (UAE), the prevalence of MetS and its features are among the highest in the world. However, research that explores the health needs of patients with MetS within the socio-cultural context of the UAE is lacking. This study aimed to explore patient and professional perceptions of MetS and its management in the UAE.